POSSIBILIDADE DE APROXIMAÇÃO DA ESCOLA E CURSO DE LICENCIATURA PELOS ESPAÇOS VIRTUAIS – ALGUMAS REFLEXÕES - Roque, Ricardo R.; Pozzobon, Marta C. C.; Battisti, Isabel K.; Roncaglio, Viviane (Salão do Conhecimento, 2013)
Resumo